2016
DOI: 10.1007/s10792-016-0230-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative factors on IOP reduction after phacoemulsification

Abstract: The purpose of the study was to determine the independent predictors of long-term intraocular pressure (IOP) reduction after cataract surgery with phacoemulsification. This is a retrospective review of uncomplicated cataract surgeries from 2006 to 2008 at the Baltimore VA Medical Center with longitudinal follow-up. Demographic, clinical, biometric, and intraoperative variables including phacoemulsification parameters were recorded. Univariate and multivariate linear regression were used to analyze the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
1
7
0
2
Order By: Relevance
“…The group with preoperative IOP ≤21mmHg had a success of 37.5% with a decrease in IOP of 11.5% (16.5 ±2.9 to 14.6 ±3.7mmHg, P=0.012) while 62.5% of those with preoperative IOPs >21mmHg achieved success with a decrease in IOP of 36.6% (25.8 ±2.9 to 16.4 ±5.4mmHg, P<0.001). This is consistent with other studies that find CE/IOL alone is more effective at IOP-lowering when performed in patients with higher preoperative IOPs[27]*. No serious complications were reported in this study.…”
Section: 0 Increasing Trabecular Outflowsupporting
confidence: 93%
See 1 more Smart Citation
“…The group with preoperative IOP ≤21mmHg had a success of 37.5% with a decrease in IOP of 11.5% (16.5 ±2.9 to 14.6 ±3.7mmHg, P=0.012) while 62.5% of those with preoperative IOPs >21mmHg achieved success with a decrease in IOP of 36.6% (25.8 ±2.9 to 16.4 ±5.4mmHg, P<0.001). This is consistent with other studies that find CE/IOL alone is more effective at IOP-lowering when performed in patients with higher preoperative IOPs[27]*. No serious complications were reported in this study.…”
Section: 0 Increasing Trabecular Outflowsupporting
confidence: 93%
“…Prior work has shown that each additional millimeter of mercury results in an 11% increase in the risk of glaucoma progression[88]*. Most MIGS studies are combined with cataract surgery, which can lower IOP in the short term by 2–4mmHg[27]*[89][90]. However, this effect wanes over time, thus studies focusing on long term data will be important moving forward.…”
Section: 0 Expert Opinionmentioning
confidence: 99%
“…Similar to Lee et al [17], our analysis failed to demonstrate any significant relationship between the amount of CDE and the IOP variations. A study by DeVience and colleagues [38] was able to show a significant correlation between phacoemulsification time and postoperative IOP reduction 24 months postoperatively. However, these findings were not confirmed by Pradhan et al [35].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the phacoemulsification ultrasound may improve trabecular meshwork aqueous drainage. DeVience et al reported that intraoperative phacoemulsification time was associated with greater IOP reduction in normal eyes . This is supported by an in‐vitro study of phacoemulsification ultrasound on trabecular meshwork cells activating cellular pathways leading to improved aqueous outflow and lower IOP .…”
Section: Discussionmentioning
confidence: 88%